Pengaruh Brand Image dan Brand Trust Terhadap Brand Loyalty PIXY Cosmetics Melalui Customer Satisfaction Sebagai Variabel Intervening. - Husnul Khatimah Khatimah; Diah Komalasari (Fakultas Ekonomi Universitas Islam 45, 2022)
This study discusses how brand image and brand trust affect brand loyalty PISY cosmetics through customer satisfaction as an intervening variable. The purpose of this study was to examine and analyze the influence of brand image & brand trust with the role of customersatisfaction as a mediation influencing brand loyalty at PIXY cosmetics in Jakarta.The sampling technique used was non-probability sampling with purposive sampling method, totaling 150 respondents were people in Jakarta. The data collection technique used a questionnaire distributed via google form. The analytical test tool used is SmartPLS 3.0.The results show that brand image has a positive and significant effecton customer satisfaction as evidenced by the t-statistic value (7,657>1,96), brand trust has a positive and significant effect on customersatisfaction seen from the value t-statistic (3,216>1,96), brand image does note have a positive and significant effect on brand loyalty as evidenced by the statistical value (1,400<1,96), brand trust does not have a positive and significant effect on brand loyalty with a statistical value (0,427<1,96), customer satisfaction has a positive and significant effect on brand loyalty with statistical value (6,314>1,96), there is a direct effect for the brand image variable on brand loyalty through customer satisfaction with a statistical value (5,075>1,96), and variable brand trust on brand loyalty through customer satisfaction acts as a full mediation.